2002
DOI: 10.1046/j.1365-2141.2002.03943.x
|View full text |Cite
|
Sign up to set email alerts
|

The naive T‐lymphocyte compartment is well preserved in patients with chronic myelogenous leukaemia in chronic phase

Abstract: Summary. In chronic myelogenous leukaemia (CML), clonal change occurs in all myeloid and B‐cell lineages, but very rarely T‐cell lineages. A detailed three‐colour cytometric analysis of peripheral lymphocytes was performed in 22 patients with chronic‐phase CML (CP‐CML). CD45 gating analysis was used to discriminate between lymphocytes and basophils. The peripheral lymphocyte pool was comprised of a significant proportion of naive CD4 cells, defined by a CD4+45RA+ phenotype [47·0 ± 19·6% (mean ± SD) of the tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 40 publications
2
8
0
Order By: Relevance
“…2A) were within the range reported by other authors for healthy subjects belonging to this age group (Isoda et al, 2002). We found a significantly diminished amount of CD4 ϩ naïve T cells in AT heterozygotes versus normal donors (p Ͻ 0.01), with only one heterozygous subject (Ht16-m, Fig.…”
Section: Lantelme Et Alsupporting
confidence: 71%
See 1 more Smart Citation
“…2A) were within the range reported by other authors for healthy subjects belonging to this age group (Isoda et al, 2002). We found a significantly diminished amount of CD4 ϩ naïve T cells in AT heterozygotes versus normal donors (p Ͻ 0.01), with only one heterozygous subject (Ht16-m, Fig.…”
Section: Lantelme Et Alsupporting
confidence: 71%
“…Again, we found that the CD8 naïve compartment in four AT heterozygotes as well as in three age-matched control subjects (Fig. 2B) was comprised within the mean value reported by Isoda et al (2002) for healthy subjects belonging to the same age group (mean Ϯ SD, 41 Ϯ 26.8%). …”
mentioning
confidence: 63%
“…At least in the case of CML, the decrease was unlikely to be caused by a reduction in the number of CD8 + leukocytes. In fact, CD8 + /CD3 + T cell ratios at different stages of CML are generally not reduced compared with those in healthy donors [45,46]. Our results also demonstrate that the intensity of the FCRL6 hybridization signals was decreased in PBMCs and CD3 + cells from patients with autoimmune diseases, such as rheumatoid arthritis, systemic lupus erythematosus, and idiopathic thrombocytopenia purpura.…”
Section: Discussionsupporting
confidence: 41%
“…In CML, the percentage of CD4+ cells is high compared to the control group in an untreated state and rapidly decreases after treatment. In contrast, the proportion of CD8 cells remains much the same throughout treatment [16]. The pathophysiology of the cutaneous manifestations to STI 571 is unclear, but as mentioned above, the increased CD8+ cell proportion with CML treatment may explain the intense cutaneous infiltration of CD8+ cells at the drug eruption site.…”
Section: Discussionmentioning
confidence: 81%